Improving Kanji Reading Ability with Poro Nihongo: A Qualitative Study Of Students’ Perceptions - Rita Arni; Reny Rahmalina; Prisyanti Suciaty; Rahmi Oktayori Wikarya; Dian Lestari (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
This study aims to explore students' perceptions of the use of the Poro Nihongo application in improving Kanji reading skills. In this era of globalization, mastery of foreign languages, especially Japanese, is very important. However, many students have difficulty in learning Kanji, due to the complex writing system. Poro Nihongo, as a game-based learning application, is designed to make the Kanji learning process more interesting and interactive.Through a qualitative approach and case study design, this study involved 70 students of the Japanese Language Education Study Program at Padang State University, with in-depth interviews conducted with 9 students representing various levels of ability. The interview results showed that students felt that Poro Nihongo helped increase their motivation and engagement in learning Kanji. Students reported improvements in comprehension, speed, and accuracy of reading Kanji after using this application.However, there were challenges faced, such as device limitations, connectivity issues, and potential interference from other applications. Some students also expressed the need for a greater variety of learning materials and support for independent learning. Although, Poro Nihongo has proven to be effective in improving Kanji reading skills, students expect the app to emphasize understanding Kanji meanings and provide better reading speed practice.This research provides valuable insights for app developers, educators, and education policymakers in designing more effective and appropriate learning methods for students in the digital age. The findings expected to contribute to the development of technology integration strategies in Japanese language learning curricula.